The quest for better economics graduates: reviving the pluralist approach in the case of the International Islamic University Malaysia - Mohd Amin, Ruzita; Haneef, Mohamed Aslam (Inderscience Publisher, 2011)
This study examines the case of the Bachelor of Economics curriculum at the International Islamic University Malaysia regarding the extent of the practice of pluralism in the quest to create better graduates professionally competent and imbued with ethical values. We conclude that the programme provides a 'model of integration' of knowledge, motivated by ideological commitment to an Islamic view of education as a process to build personality and character via the provision of knowledge, skills and values. The programme shows the practice of 'permissive' pluralism in the early years, has reverted to a more standardised mainstream neoclassical curriculum. We also argue that adopting a pluralist position can actually contribute to the development of an Islamic economics alternative. Tracer studies have shown that the integration model is somewhat successful in producing qualified professionals, concomitantly imbued with ethical values of Islam